A classification and prediction based approach for real-time ETP outlet monitoring through E-IoT and remote sensing using machine learning and deep learning - Hossain, Md. Mehedi; Mridha, Md. Jahid Hasan; Imran, Sazid Md.; Wahid, SK Ayub Al (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.